A New Zinc(II) Coordination Polymer with Two-Dimensional sql Topology Based on Asymmetrically Tricarboxylate and Nitrogen-Containing Ligand - Xu, Liping (Asian Journal of Chemistry, 2014)
A new coordination polymer [Zn(Hbtc)(bpmp)0.5]·H2On (1) [H3btc=biphenyl-3,4',5-tricarboxylate and bpmp=1,4-bis(4-pyridylmethyl)-piperazine] has been obtained under hydrothermal conditions. Complex [Zn(Hbtc) (bpmp)0.5]·H2On (1), is triclinic, space group P-1 with a = 8.189 (5) Å, b = 8.919 (5) Å, c = 15.998 (5) Å, b = 90.622 (5)°V =1050.9 (9) Å3, Z = 2, Mr = 501.78, Dc = 1.586g/cm3, F(000) = 516 and μ = 1.22 mm-1. The final refinement gave R = 0.0483 and wR = 0.1187 for 2390 reflections with I > 2s (I). X-ray diffraction analysis reveals that complex 1 shows a two-dimensional (4,4) sql layer.